Affordable housing performance assessment: applying the concept of grow home as one of the measurement criteria - Ahlam Mohammad Jamal Esruq-Labin,; Ahmad Rafizi Salleh,; Halizah Omar,; Adi Irfan Che-Ani,; Norngainy Mohd Tawil, (Penerbit Universiti Kebangsaan Malaysia, 2016)
In an attempt to fulfill the basic needs of proper accommodation for its people, governments of all countries strive to ensure that every household is able to have a home. Thus, the concept of affordable housing has become widespread around the world. In addition, the concept of Grow Home was established to encourage more families to buy their own houses. The Grow Home concept is based on the notion of affordable housing. This article aims to consider the concept of Grow Home as one of the Affordable Housing Performance Assessment for the landed housing in the central region of Peninsular Malaysia. It consists of two criteria; landed properties and new spaces. Taman Selasih and Taman Lukut Makmur, constructed in Negeri Sembilan, the central region of Peninsular Malaysia were chosen for the case study.The sample consists of 155 units in Taman Selasih and 93 units in Taman Lukut Makmur. A physical survey was conducted to assess the grow home measurement item in Taman Selasih and Taman Lukut Makmur through field observation and informal interviews with the residents at the site. The findings from this case study showed that Grow Home could be considered as an affordable housing performance assessment since the criteria of landed properties and new spaces affect the housing industry performance as a whole.